The Effectiveness of Indonesia's Anti-Corruption Law on Legal Reform and Implementation - Tomagola, Ardy Gunawan; Yaurwarin, Wahid; Rahajaan, Jakobus Anakletus; Sahetapy, Agustinus Jonas; Kalauw, Reni Wahyuni (West Science Law and Human Rights, 2024)
This study examines the efficacy of Indonesia's anti-corruption legislation in the wider framework of legislative restructuring and its execution. The paper investigates the legal frameworks and regulatory measures implemented to combat corruption, using a normative juridical analysis. The primary objective is to examine the impact of these laws on legal reform, evaluate their enforcement, and highlight the problems encountered in their practical implementation. The results demonstrate substantial advancements in legislative actions, but also underscore enduring barriers in execution, such as legal ambiguities, administrative stagnation, and corruption within law enforcement entities. This study highlights the importance of implementing comprehensive legal reforms and strong policies to improve the effectiveness of anti-corruption measures in Indonesia. Guidelines are given to promote future anti-corruption efforts by improving the legislative framework, increasing institutional capability, and cultivating political backing.